Who Are Active and Inactive Participants in Online Collaborative Writing? Considerations From an EFL Setting - Nakhon Kitjaroonchai; Daron Benjamin Loo (ACADEMY PUBLICATION, 2023)
This study investigated learners’ online collaborative writing (CW) behaviours. The participants were 115 EFL students from different Asian countries at a private international university in Thailand. The quantitative data was collected from students’ writing contributions on two collaborative writing tasks: descriptive and argumentative essays. Data was analyzed using one-way analysis of variance (ANOVA) and the Bonferroni Post Hoc Test. The analysis from the one-way ANOVA test revealed a significant difference between groups regarding percentage of text contribution in CW tasks. Qualitative data was also collected from students’ reflective journals and observations, where factors that influenced team collaboration were examined. The qualitative findings showed that students with higher language proficiency levels were the prominent authors who contributed more text to their group tasks. Elements affecting learners’ active and inactive participations in team collaborations include student language proficiency, individual goal, designated roles, collaboration platforms, learning preference, topic familiarity, and influence of teacher. Some implications of the findings are discussed.